Effect of Ingredients Formulation Of Mechanics Traits on Organic Planting Bag - Nugroho, Wahyunanto Agung; Rahayu, Febi Damayanti; Lutfi, Musthofa (Jurnal Teknologi Pertanian, 2013)
The use of planting bags of organic materials in the field of agriculture is a solution to problems such as stacking plastic bag after the seedling planting is completed and inhibits plant growth due to wrong release of planting bag. Organic planting bag practices can add nutrients to the soil and has the ability to retain water, which supports the growth and development of plants. The purpose of this study is to modify the organic planting bags that have been developed using material compositions and sizes of planting bag. The research was conducted in two phases, namely the manufacture and testing of organic planting bag. Parameters observed in this study is the water content, vertical pressure testing, tensile testing, volume and mass of planting bag. Based on the results of LSD test showed that the combined treatment of combination treatment A6B6 is best used as an ingredient of organic planting bag where the comparison between coconut husk and water hyacinth at 1:7.25. To test the moisture content value obtained was 82.35%, for testing the vertical pressure is 0007 kg/cm2, and for testing the tensile stress is 0067 kg/cm2.Keywords: Organic Plnating Bag, Water hyacinth, Coconut Husk